Effects of doping with manganese on the optical properties of magnesium aluminate spinel crystals - Gritsyna, V.T.; Kazarinov, Yu.G.; Kol'ner, V.B.; Lytvynov, L.A.; Sickafus, K.E. (Functional Materials, 2005)
The effects of doping with manganese ions on the optical properties of magnesium aluminate spinel crystals grown by Czochralski method were investigated. The optical spectra of the doped crystals have intense absorption in the range of 4.5-6.7 eV which was fit with three absorption bands; the intensity and energy position of these bands vary in dependence on the concentration of doping ions. This effect is explained by formation of F-type centers near the incorporated Mn ions which leads to changes of electronic properties of F⁺ -centers and formation of complex defects including Mn-ions. The neutral atmos- phere of crystal growth in Czochralski method stimulates the formation of anionic vacancy trapped one electron (F+-center). Radio- and photoluminescence spectra demonstrate the bands related to the recombination luminescence at antisite defects, to emission of impurity ions Mn²⁺ and Сг³⁺ - ions, parameters of which indicate the processes of segregation and coagulation antisite defects during the growth of spinel crystals. Дослiджено вплив активацiї iонами марганцю на оптичнi властивостi кристалiв магнiй-алюмiнiевоl шпiнелi, вирощених методом Чохральського. Оптичнi спектри активованих кристалiв мiстять iнтенсивне поглинання в областi 4.5-6.7 еВ, яке є суперпозицiєю трьох смуг поглинання, iнтенсивнiсть та спектральне положення яких змiнюються в залежностi вiд концентрацiї активаторних iонiв. Цей ефект пояснюється створенням F-типу центрiв, розташованих поблизу iонiв марганцю, що призводить до змiни електронних властивостей F⁺-центрiв та створення комплексiв дефектiв до яких входять iони марганцю. Нейтральне середовище вирощування кристалiв за методом Чохральського зумовлюе створення анiонних вакансiй, якi захоплюють один електрон (F⁺ - центри). Спектри рентгено- та фотолюмiнесценцil мiстять смуги, якi вiдносяться до рекомбiнацiйної люмiнесценцiї на дефектах антиструктури, випромiнювання домiшкових iонiв Mn²⁺ та Сг³⁺, параметри яких вказують на наявнiсть процесiв сегрегацil та коагуляцil дефектiв антиструктури у процесi росту кристалiв шпiнелi. Исследовано влияние активации ионами марганца на оптические свойства кристаллов магний-алюминиевой шпинели, выращенных методом Чохральского. оптические спектры активированных кристаллов содержат интенсивное поглощение в области 4.5- 6.7 эВ, которое представляет суперпозицию трех полос поглощения, интенсивность и спектральное положение которых изменяются в зависимости от концентрации активаторных ионов. Этот эффект объясняется образованием F-типа центров, расположенных вблизи ионов марганца, что приводит к изменению электронных свойств F⁺ - центров и образованию комплексов дефектов, включающих ионы марганца. Нейтральная среда выращивания кристаллов по методу Чохральского обусловливает образование анионных вакансий, захвативших один электрон (F⁺ - центры). Спектры рентгено- и фотолю- минесценции содержат полосы, относящиеся к рекомбинационной люминесценции на дефектах антиструктуры, а также к излучению примесных ионов Mn²⁺ и Сг³⁺, параметры которых свидетельствуют о наличии процессов сегрегации и коагуляции дефектов антиструктуры в процессе роста кристаллов шпинели.